A Novel Cogging Torque Simulation Method for Permanent-Magnet Synchronous Machines - Chun-Yu Hsiao (Energies, 2011)
Cogging torque exists between rotor mounted permanent magnets and stator teeth due to magnetic attraction and this is an undesired phenomenon which produces output ripple, vibration and noise in machines. The purpose of this paper is to study the existence and effects of cogging torque, and to present a novel, rapid, half magnet pole pair technique for forecasting and evaluating cogging torque. The technique uses the finite element method as well as Matlab research and development oriented software tools to reduce numerous computing jobs and simulation time. An example of a rotor-skewed structure used to reduce cogging torque of permanent magnet synchronous machines is evaluated and compared with a conventional analysis method for the same motor to verify the effectiveness of the proposed approach. The novel method is proved valuable and suitable for large-capacity machine design.